Effects of dietary electrolyte balance and calcium supply on mineral and acid−base status of piglets fed a diversified diet. (2020) - Bournazel, M.; Duclos, M. J.; Lecompte, F.; Guillou, D.; Peyronnet, C.; Quinsac, A.; Même, N.; Narcy, A.
Abstract: Dietary electrolyte balance (dEB) is known to affect acid−base status and mineral metabolism, but is rarely considered in diet formulation for pigs. Yet, the use of a wide variety of local feedstuffs in Europe contributes to lowering the dEB and increasing the fibre content. Hence, mineral requirements may be modified and skeletal health affected. Therefore, the effects of a lower dEB and a higher dietary Ca level on acid−base balance and mineral status were assessed in young pigs fed a diversified diet. A total of twenty-four weaned pigs were fed a control moderate-dEB diet (C) or a diversified moderate-dEB (D), low-dEB (D-A) or low-dEB supplemented with Ca (D-CA) diet. Growth performance, venous blood gas and chemistry, urine pH, mineral balance and femur characteristics were determined. With an equivalent dEB compared with the C diet, the D diet caused an acidification of the urine and increased the excretion of P as a result of a higher dietary content of S. Low-grade metabolic acidosis occurred in piglets fed the D-A diet with changes at systemic and urine levels. A higher excretion of ammonia and P in urine was observed and some bone characteristics tended to be negatively affected. Ca supplementation partially counteracted the effects of low-grade acidosis. Urine excretion of P and ammonia was alleviated and bone characteristics improved. In conclusion, a higher Ca supply must be considered in more diversified diets to counteract the risk of evolving towards low-grade metabolic acidosis which can negatively affect bone.